Agreement Between the Pediatric Symptom Checklist-17 (PSC-17) and Clinical Psychological Evaluation in Child Sexual Abuse Victims: A Clinical Forensic Study - Ruslan; Masadah, Rina; Afandi, Ichlas N.; Zainuddin, Andi A.; Muthaher, Annisa A.; Ahmad, Djumadi (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Forensic examination of child victims of sexual abuse mainly prioritizes the identification and documentation of physical findings for legal purposes. As a result, psychosocial problems may remain underrecognized during the initial assessment. A brief and practical screening instrument is therefore needed to support early detection in clinical forensic services. To assess the agreement between Pediatric Symptom Checklist-17 (PSC-17) screening results and clinical psychological evaluation findings in child victims of sexual abuse. Methods: This analytical observational study used a cross-sectional design and was conducted from April to September 2025 at a forensic referral hospital. A total of 101 child victims of sexual abuse aged 1−17 years underwent PSC-17 screening. Clinical psychological evaluation was subsequently completed for 51 respondents, depending on the referral pathway and service availability. Agreement between PSC-17 classification and clinical psychological evaluation was assessed using a 4 × 4 contingency matrix and Cohen’s kappa coefficient. The 95% confidence interval was estimated using bootstrap analysis with 1,000 replications. Results: Of the 101 respondents, 39 children (38.6%) were classified as having severe psychosocial problems based on the PSC-17 classification applied in this study. Among the 51 respondents who underwent clinical psychosocial evaluation, 26 children (51.0%) were classified as having severe psychosocial problems. Classification accuracy was 86.27%, with a Cohen’s kappa of 0.778 (95% CI [0.606, 0.908], p < 0.001), indicating substantial agreement between PSC-17 screening and clinical psychological evaluation. Conclusion: PSC-17 showed good agreement with clinical psychological evaluation in identifying psychosocial problems among child victims of sexual abuse. These findings support its potential use as an initial screening tool to facilitate early detection and psychosocial triage in clinical forensic settings.